Comparation of Learning Outcomes Based on Identity Statuses - Tlonaen, Zuvyati Aryani; Bil Haq, Aniq Hudiyah (Jurnal Pendidikan Indonesia, 2022)
Identity status is a categorization of self-identity that helps a person to make choices based on the results of exploration and commitment. Learning outcomes vary for each students. Some students achieve excellent grade, others are average or even poor. Identity status may haveaneffecton students’ learning outcomes. This study aims to compare students' learning outcomes based on their identity statuses. This research used a quantitative approach. To examine the hypothesis, researchers used the one-way ANOVA test to answer the research question about a significant difference between students' learning outcomes and their identity status. The samples were 74 third semester students from the English Education Study Program. Data for identity statuses were obtained using a questionnaire with 40 statements. Data for learning outcomes were obtained from final semester test scores. ANOVA test result indicated a significant difference between students' learning outcomes and their identity status. Thus, this study proved that there is a difference between learning outcomes based on identity Status. Therefore, it is vital to know the students' identity status to improve student learning outcomes. Students with a diffusion identity status are in a serious problem. Teachers must find a solution so that their identity status can develop towards a high identity status.